2020
DOI: 10.1039/c9tc05829j
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal ionic self-assembly and anion-selective photoluminescence in discotic azatriphenylenes

Abstract: We report on the straightforward synthesis of a new series of ionic discotic liquid crystals based on positively charged azatriphenylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…In this subsection, the last developments regarding the synthesis of novel discotic mesogenic materials will be described. Triphenylene derivatives still remain the most studied compounds and they have been used to develop new materials, testing new side chains, or new cores [ 191 , 192 , 193 , 194 , 195 , 196 ], to be linked with other cores to prepare dyads and triads [ 67 , 197 , 198 , 199 , 200 ] or materials giving segregate columns [ 201 , 202 ]. Triphenylenes were also doped with nanoparticles or used to prepare blends with other mesogenic molecules [ 203 , 204 , 205 ].…”
Section: Recent Advances In the Study Of Discotic Liquid Crystalsmentioning
confidence: 99%
“…In this subsection, the last developments regarding the synthesis of novel discotic mesogenic materials will be described. Triphenylene derivatives still remain the most studied compounds and they have been used to develop new materials, testing new side chains, or new cores [ 191 , 192 , 193 , 194 , 195 , 196 ], to be linked with other cores to prepare dyads and triads [ 67 , 197 , 198 , 199 , 200 ] or materials giving segregate columns [ 201 , 202 ]. Triphenylenes were also doped with nanoparticles or used to prepare blends with other mesogenic molecules [ 203 , 204 , 205 ].…”
Section: Recent Advances In the Study Of Discotic Liquid Crystalsmentioning
confidence: 99%
“…Based on the recently developed synthesis of (tetraalkoxy)biphenyl-Br/biphenyl-Bpin building blocks, 43,44 various butterfly-shaped p-conjugated molecules (see Chart 1 for some thiophene-containing representative examples) can be synthesized in two steps by Pd-catalyzed Suzuki-Miyaura coupling [45][46][47] and FeCl 3 -promoted Scholl cyclo-dehydrogenation reactions tandem. [48][49][50][51][52][53][54] Here, di-and tetrabromodibenzothiophenes 55 were used as starting reagents, and coupled with biphenyl-2-boronic and Subsequently, Scholl oxidative cyclodehydrogenation by FeCl 3 generated the corresponding homologous fused DTPTBn and DTPTAn compounds. It is worth noting that a primary study showed that DTPTBn displayed high phase transition temperatures and so compounds with longer alkoxy chains were synthesized (n = 12, 14, 16) in order to decrease the temperatures; in contrast, since DTPTAn isomers showed low phase transition temperatures, only short-chain homologues were synthesized (n = 12, 10, 8).…”
Section: Resultsmentioning
confidence: 99%
“…A whole series of discotic azatriphenylene ILCs reported by Donnio displays columnar phases, however both the length of the N ‐alkyl unit and the counterion determines the mesophase geometry (Figures 14 and 15). [132] N ‐Methyl derivatives with small counterions preferably self‐assemble into rectangular lattices, whereas larger anions produce two interconnected hexagonal lattices. Furthermore, an anion‐selective photoluminescence was detected, where replacement of spherical counterions by bulky sulfonates leads to a blue shift of the emission in thin films from 550 nm to 500 nm, while the solution emission remained almost constant around 530 nm.…”
Section: Novel Mesogensmentioning
confidence: 99%
“… Schematic views of the likely supramolecular organizations. The figure was taken and adapted from ref [132] . with permission from Taylor & Francis.…”
Section: Novel Mesogensmentioning
confidence: 99%
See 1 more Smart Citation